Behavioral Economics Behind Digital Banking Adoption and Retention in the Philippines - Arriola, Brix Refil (Future Science / FSH-PH Publications, 2025)
The account ownership in digital-only banks has marked a significant growth since the Bangko Sentral of Pilipinas (BSP) has exclusively segmented these banks apart from the traditional ones in November 2020. This warrants the probe on the behavioral economics behind digital banking adoption and retention in the Philippines to examine how cognitive biases play in one’s decision to use and continually patronize digital-only banks. Grounded on Prospect Theory, Technology Acceptance Model (TAM) and Psychological Ownership Theory, the researcher administered survey questionnaires to 385 Filipino users of the digital-only banks. Descriptive-correlational research has been employed with the use of robust statistical testing such as PERMANOVA and Spearman’s rho. The findings of the study reveal that young, predominantly female, college-educated, lower- to middle-income adults characterized the primary adopters, though their engagement remained tentative. Behavioral constructs, adoption and retention drivers consistently drew neutral responses, suggesting cautious acceptance rather than enthusiasm. However, behavioral factors strongly influenced younger, self-employed, and lower-income users, whereas higher earners and those with higher educational attainment relied more on logical evaluation, financial benefits, and product-specific features, indicating varying motivations shaped by demographic intersections. This outcome calls for a more tailored customer experience so Filipinos can be enticed to adopt and retain digital banking services rather than a one-size-fits-all solution. This behavioral split unearths that some users crave control and confidence whilst the other seek connection and ease. Implications and recommendations have been provided in the end to help further the adoption and retention of digital banking services in the Philippines.